Cyclic Voltammetric study of 4'-Chloro-2-Hydroxy-4-Methoxybenzophenone - Moses, G.S.; Rao, K.M.; Douglas, S.P.; Reddy, J.M.S. (Asian Journal of Chemistry, 2010)
The electrochemical reduction of carbonyl group present in 4´-chloro-2-hydroxy-4-methoxybenzophenone has been studied employing cyclic voltammetric technique in 40% (v/v) ethanolwater and DMF-water mixures in the pH range 4.0–11.8. The reduction of keto group follows one electron irreversible reduction process in the pH range 4.0–8.2 and two electron irreversible reduction process in the above pH range studied. The effect of solvent on the reduction process is discussed. The diffusion coefficient and forward rate constant values have been evaluated and a suitable reduction mechanism is proposed.